Criminal Law Enforcement Against Perpetrators of Sexual Intercourse with Biological Children - I Ketut Agus Suartana (International Journal Labs, 2024)
Criminal law enforcement is important in dealing with cases of incestuous sexual relations involving children, aiming to uphold justice and protect victims from harm. The main objective of this study is to examine the effectiveness of law enforcement in the jurisdiction of Tabanan Police in handling cases. Using empirical research methods, this study analyzes legal principles such as the rule of law, legislation theory, legal protection, legal responsibility, and legal effectiveness. This research focuses on a specific case documented in Police Report No. LP-B/35/VII/2020/B: LP-B/35/VII/2020/Bali/Res Tbn, in which the perpetrator, MSP, was charged with violating Article 81(3) of the Child Protection Law, in conjunction with Article 64(1) of the Criminal Code, or alternative provisions under the law. The results showed that there are significant challenges hindering effective law enforcement, particularly the lack of qualified law enforcement officers compared to the number of cases, which hinders optimal case handling in the jurisdiction of Tabanan District Police. This research argues that effective law enforcement is essential not only to sanction perpetrators but also to ensure justice and protect child victims from violence and crime. The implications of this study underscore the need for increased competence among law enforcement officials to effectively handle such sensitive cases. By bridging the gap between legal provisions and law enforcement, this research advocates for systemic improvements to strengthen the law enforcement framework in combating the crime of incest against children.